PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS VIII SMPNEGERI 4 MANIAMOLO PADA MATERI SISTEM PENCERNAAN MANUSIA - Dachi, Anidalai (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The background to the problem is that the learning process is still teacher-centered and does not involve students taking an active role in the learning process, students do not understand the material about the human digestive system, and student learning outcomes are low. This research aims to determine whether there is an influence of the problem based learning model on the learning outcomes of class VIII students at SMP Negeri 4 Maniamolo. This type of research is quasi experimental. The population of this study was class VIII students at SMP Negeri 4 Maniamolo. This research data was analyzed using the normality test, homogeneity test and hypothesis test using the SPSS 2.1 application. The results of this study showed that the average initial test for the control class was 65.38 while for the experimental class it was 66.33. The final test average of the control class was 74.23 while the experimental class was 80.00. From the student learning results in these two classes, there is an influence of the problem based learning model on the learning outcomes of class VIII students at SMP Negeri 4 Maniamolo. It can be said that the control class and experimental class have more students who meet the KKM score using the problem based learning model compared to student learning outcomes using the conventional model and while participating in learning activities using the problem based learning model students understand better which can be seen in the student learning outcomes with final test of experimental class. The material in this research is the human digestive system, which is the process carried out by the digestive tract in the human body so that food can be processed and absorbed by its nutrients and turned into energy. So it can be concluded that students are able to develop creative thinking skills and are able to solve the problems faced or discussed. Researcher suggestions (1) teachers should use varied learning models such as problem based learning models to improve student learning outcomes and be able to think critically, creatively and actively. (2) Researchers should carry out this research with reference source materials and broader insight.